2018
DOI: 10.1017/s0022029918000110
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNP and STR polymorphisms of insulin-like growth factor 2 receptor (IGF2R) gene with milk traits in Holstein-Friesian cows

Abstract: The objective of the study reported in this Research Communication was to investigate the association of polymorphisms in the insulin-like growth factor receptor 2 (IGF2R) gene with milk traits in 283 Polish Holstein-Friesian (PHF) cows from the IGAB PAS farm in Jastrzębiec. IGF2R regulates the availability of biologically active IGF2 which is considered as a genetic marker for milk or meat production in farm animals. Two novel genetic polymorphisms were identified in the bovine IGF2R gene: a polymorphic TG-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…With the recent development of analytical tools and genomic resources, it is possible to identify Quantitative Trait Loci (QTL) and thus, study the influence of multiple genes on biological traits and milk composition (Dux et al ., 2018). Thus, QTL could contribute to find genes that can be used in breeding programs via marker-assisted selection.…”
Section: Strategies To Modify the Milk Protein Composition: Animal Gementioning
confidence: 99%
“…With the recent development of analytical tools and genomic resources, it is possible to identify Quantitative Trait Loci (QTL) and thus, study the influence of multiple genes on biological traits and milk composition (Dux et al ., 2018). Thus, QTL could contribute to find genes that can be used in breeding programs via marker-assisted selection.…”
Section: Strategies To Modify the Milk Protein Composition: Animal Gementioning
confidence: 99%
“…and LEP genes in cattle may influence the milk traits, feed intake, milk fatty acid composition and metabolic state (Avondo et al, 2019 ;Dux et al, 2018 ). Therefore, they are important targets to inform breeding practices.…”
Section: Discussionmentioning
confidence: 99%
“…Karim and his colleagues found that SSRs in PLAG1‐CHCHD7 intergenic region can affect promoter activity and influence the binding of nuclear factor (Karim et al., 2011). Not only that, the SSRs of IGF2R and LEP genes in cattle may influence the milk traits, feed intake, milk fatty acid composition and metabolic state (Avondo et al., 2019; Dux et al., 2018). Therefore, they are important targets to inform breeding practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in recent decades, quantitative trait locus (QTL) mapping, candidate gene analysis, genome-wide association analysis and high-throughput sequencing techniques have been widely used in dairy cow breeding to identify the functional elements [6][7][8][9][10]. Moreover, studies have shown that SNPs (single nucleotide polymorphisms) in the gene can significantly affect the milk production traits of dairy cows [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%